Decreasing disruptive behaviour during routine dental visits: a video modelling intervention for young children. (29th November 2018) - Hine, Jeffrey F.; Hajek, Ryan T.; Roberts, Holly J.; Allen, Keith D.
Abstract : Objective: To evaluate the benefits of a collaborative partnership between paediatric dentists and behavioural health providers in which a practical video modelling intervention, with the aim to reduce disruptive behaviours in young children, is implemented. Methods: The video was created by a dentist using readily available technology and implemented in a busy practice setting. A clinical sample of 40 children, 3–6 years old, was recruited from a continuous sample of patients seen at the clinic. Participants were randomised into two groups and shown either the brief video model or a control video prior to a routine dental visit. All sessions were videotaped and independently scored by blinded observers. Behavioural data were recorded using 15‐second partial‐interval recording and included physical and vocal disruptions. Subjective measures of cooperation were also completed by observers and dental professionals. Results: Independent samples t ‐tests show that the treatment group had a significantly lower mean percentage of intervals in which disruptive behaviour was observed [ t (38) = 2.94, P = 0.008] compared with the control group. Subjective rating scales revealed significantly higher ratings of cooperation for the treatment group from the dentist [ t (38) = −5.19, P = 0.000], the dental assistant [ t (38) = −4.01, P = 0.001] and the blinded coder [ t (38) = −3.54, P = 0.002]. Significant relationships were found between the percentage of actual disruptive behaviour and subjective ratings of the dentist ( r = −0.82, P < 0.01). Conclusions: Watching a brief dentist‐created video model of expected procedures can reduce disruptive behaviour and increase cooperation for young children making their first visit to a busy medical setting.